2020
DOI: 10.1084/jem.20191236
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of human monocytes and airway macrophages during healthy aging and after transplant

Abstract: The ontogeny of airway macrophages (AMs) in human lung and their contribution to disease are poorly mapped out. In mice, aging is associated with an increasing proportion of peripherally, as opposed to perinatally derived AMs. We sought to understand AM ontogeny in human lung during healthy aging and after transplant. We characterized monocyte/macrophage populations from the peripheral blood and airways of healthy volunteers across infancy/childhood (2–12 yr), maturity (20–50 yr), and older adulthood (>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
122
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(134 citation statements)
references
References 44 publications
2
122
2
Order By: Relevance
“…Four subpopulations of macrophages/monocytes were found. Among them, 3 subpopulations corresponded to AMs based on their expression of MARCO (25,27). AMs are the most abundant cells found in the airways in homeostatic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Four subpopulations of macrophages/monocytes were found. Among them, 3 subpopulations corresponded to AMs based on their expression of MARCO (25,27). AMs are the most abundant cells found in the airways in homeostatic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In each cluster, a selection of the most overexpressed transcripts able to differentiate cell types according to the literature is displayed in Table 3. Cells of clusters 0, 3, 5, and 8 expressing MARCO and/or MSR1 and/or HLA-DRB1 and/or CD163 and/or CD86 and/or MRC1 and/or CD68 and/or CD63 were identified as macrophages/monocytes (25)(26)(27)(28)(29)(30)(31)(32). Cells of cluster 1 and 2 expressing CD3 markers were identified as T lymphocytes (28,33).…”
Section: Single-cell Rna Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…40 The human AM population was therefore assumed to be much more dynamic and unstable than that observed in mice. 40 Pulmonary macrophages, more specifically AMs, can control lung-resident memory T cells (TRMs). 41 TRMs are perfectly positioned to mediate rapid protection against respiratory pathogens such as coronavirus.…”
Section: Lung Parenchyma Local Immunitymentioning
confidence: 99%
“…Nevertheless, recent transplantation studies have provided some new views and have shown that donor-derived macrophages persist for many years in transplanted skin or liver in patients [29]. Furthermore, lung macrophages can self-renew for years in a murine model [30,31], but recent work on alveolar macrophage ontogeny in the human lung during healthy aging and after transplant suggests that donor alveolar macrophages are quickly replaced from the recipient peripheral circulating monocytes [32]. Interestingly, the human myocardium contains two distinct subsets of macrophages: CCR2− and CCR2+ (C-C chemokine receptor type 2).…”
Section: Originmentioning
confidence: 99%